 # 8x squared to the fourth power of Y (minus 3x divided by the sixth power of 4Y) * {- 6Z / x ^ y} Add the fourth power of 5C / 2A ^ B / (- 6ab's sixth power, C's Square) / (20c's third power / 3A's third power, B's tenth power)

## 8x squared to the fourth power of Y (minus 3x divided by the sixth power of 4Y) * {- 6Z / x ^ y} Add the fourth power of 5C / 2A ^ B / (- 6ab's sixth power, C's Square) / (20c's third power / 3A's third power, B's tenth power)

Hello: 8x square y to the fourth power (minus 3x divided by the sixth power of 4Y) * {- 6Z / x ^ y} = - 6x ³/ y ²* （-6z/x ² y）=-36xz/y ³ If you don't understand this question, you can ask. If you are satisfied, please click "select as satisfactory answer". If you have other questions, please adopt this question and send it to me again

### Square of {x-square of 3xy-4y = 0 {X-Y = 3

From (1)
(x-4y)(x+y)=0
x-4y=0 x+y=0
And equation (2) can form two equations
x-4y=0 x+y=0
x-y=3 x-y=3
∴x=4 x=3/2
y=1 y=-3/2

### X * x + 3xy-4y * y = 0 (X-Y) / (x + y) Just give me some ideas

x ²+ 3xy-4y ²= 0
(x+4y)(x-y)=0
So x = - 4Y, or x = y
When x = - 4Y, (X-Y) / (x + y) = - 5Y / - 3Y = 5 / 3
When x = y, (X-Y) / (x + y) = 0
So (X-Y) / (x + y) = 0 or 5 / 3

### How to transform a decomposition formula into a genetic formula, for example, how to transform x square + 3xy-4y square = 0 into (x + 4Y) (X-Y) = 0, is there any method? I can't try one by one... Is there any formula?

cross multiplication
X square + 3xy-4y
1（x） 4
1 (x) -1
(x+4y)(x-y)=0
The coefficient of X squared is divided into 1 × The coefficient of 1 -4y is divided into 4 × （-1）
Then cross multiply by 1 × （-1）+1 × 4 = 3 (coefficient of 3xy)

(x-4y)(x+y)=0
x=4y x=-y
∴x/y=4 x/y=-1

### (square of X - square of 4Y) / (x + y) ÷ (square of X - 2XY) ÷ (square of X + square of xy-2y) / (square of X - square of Y)

=(x+2y)(x-2y)/(x+y) × 1/x(x-2y) × (x+y)(x-y)/(x+2y)(x-y)
=1/x